PERANCANGAN PROYEK ARSITEKTUR INTERIOR STB SUPERMARKET DI TARAKAN - Caroline, Senny; Kusumowidagdo, Astrid; Indrawan, Stephanus Evert (Aksen : Journal of Design and Creative Industry, 2020)
Public awareness for healthy living, especially in big cities is increasing. Increasing economic status and ease of access to information and knowledge about healthy lifestyle make people, especially people with middle class economies, begin to pay more attention to health. One of the efforts made to start a healthy life is through organic food products. Organic food products are high-quality natural food ingredients containing vitamins, fiber, minerals, and other substances that are useful for consuming and consuming. The awareness of these qualities makes the product more organic in demand. Shopping for food needs a common thing for people to do. The development of lifestyle also affects the community in determining shopping places. The growing age makes retail businesses change the retail concept to be more modern. The concept of supermarkets is now a demand for changes in the lifestyle of the city. The retail concept is now focused on large and wide sales area outlets and facilities for convenience and comfort that are comfortable and have an impact on sales. Seeing this developing a supermarket with organic products and paying attention to the opportunity to develop a supermarket business. The interior architectural design concept of the STB Supermarket is designed to provide a fresh impression to organic support, which is a combination of centralized and grid circulation patterns, and circulation separation. Supermarket visitors, employees, and management staff can be more effective. Keywords: Healthy Product, Lifestyle, Organic, Retail, Supermarket